2008
DOI: 10.1111/j.1600-0501.2008.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture force of tooth–tooth‐ and implant–tooth‐supported all‐ceramic fixed partial dentures using titanium vs. customised zirconia implant abutments

Abstract: All restoration alternatives showed sufficient fracture resistance for posterior regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
1
24
2
1
Order By: Relevance
“…These values are comparable to those in the present study (1,738-2,354 N). This was even higher than values found for three-unit-FDPs made of lithium disilicate glass-ceramic (950 N) 23) , In-Ceram Alumina (851 N) 24) , In-Ceram Zirconia (841 N) 24) , and zirconia (981-1331 N) 23,25) . In contrast, composite-and PMMAbased three-unit FDPs showed much lower mean fracture loads ranging from 268 N to 467 N 5) .…”
Section: Discussionmentioning
confidence: 58%
“…These values are comparable to those in the present study (1,738-2,354 N). This was even higher than values found for three-unit-FDPs made of lithium disilicate glass-ceramic (950 N) 23) , In-Ceram Alumina (851 N) 24) , In-Ceram Zirconia (841 N) 24) , and zirconia (981-1331 N) 23,25) . In contrast, composite-and PMMAbased three-unit FDPs showed much lower mean fracture loads ranging from 268 N to 467 N 5) .…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, Palmer et al suggested a temperature range of 0 to 67°C for thermal stressing [22]. Thermal cycling between 5 and 55°C lies near the limits of this range and has already been performed by several other investigators [8,12,23,24]. In addition, according to Gale et al, 10,000 thermal cycles corresponds to approximately 1 year of function [25].…”
Section: Discussionmentioning
confidence: 89%
“…Five were clinical reports [2,6,8,18,24] and 35 were papers on PEEK surface treatments [13][14][15][16][17] how the bioactivity of PEEK can be improved [1,21]; the characteristics of CFR-PEEK [3,7,[19][20]; the biocompatibility of PEEK [5]; PEEK applications [4,8,[10][11]30]; PEEK biofilm formation [22,[31][32][33][34], PEEK as an abutment material and as an implant material [12,23,[25][26][27][28][29]35,40] and the use of CAD-CAM with PEEK [36][37][38][39]. …”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…It has been reported that the fracture resistance of the CAD-CAM milled PEEK fixed dentures is much higher than that of alumina, zirconia and lithium disilicate glass-ceramic [39][40].…”
Section: Peek and Cad-cammentioning
confidence: 99%
See 1 more Smart Citation